Effect of computer-aided management on the quality of treatment in anticoagulated patients: a prospective, randomized, multicenter trial of APROAT (Automated PRogram for Oral Anticoagulant Treatment) - Manotti, C; Moia, M; Palareti, G; Pengo, V; Ria, L; Dettori, AG (Haematologica (Roma), 2001)
Centro Malattie Emostatiche, Azienda Ospedaliera di Parma, Via Gramsci, 16, I-43100, Parma, Italy. cmanotti@ao.pr.it BACKGROUND AND OBJECTIVES: We carried out a prospective, randomized trial to test whether a computer-based decision support system to initiate and maintain oral anticoagulant (OA) treatment can improve the laboratory quality of therapy. DESIGN AND METHODS: Two separate sets of patients on oral anticoagulants, in five Italian anticoagulant clinics, were studied: 335 patients in the first three months of treatment (stabilization phase), 916 patients (775 patient-years) beyond the third month of treatment (maintenance phase). Patients were randomized to a computerized system, which included algorithms able to suggest OA dosing and to schedule appointments (computer-aided dosing) or to an arm in which OA were prescribed by the same teams of expert physicians without such algorithms (control group). Primary outcomes were: A) the percentage of patients reaching a stable state of anticoagulation during each of the first three months of treatment; B) the percentage of time individuals spent within the aimed therapeutic range (maintenance phase). RESULTS: Patients in the computer-aided dosing group achieved a stable state significantly faster (p